Explaining exchange rate risk in world stock markets: A panel approach - Patro, Dilip K.; Wald, John K.; Wu, Yangru (Journal of Banking & Finance, 2002)
Using a GARCH approach, we estimate a time-varying two-factor international asset pricing model for weekly equity index returns of 16 OECD countries. A trade-weighted basket of exchange rates and the MSCI world market index are used as risk factors. We find significant currency risk exposures in country equity index returns. We then explain these currency betas using several country-specific macroeconomic variables with a panel approach. We find that imports, exports, credit ratings, and tax revenues significantly affect currency risks in a way that is consistent with some economic hypotheses. Similar conclusions are obtained by using lagged explanatory variables, and thus these macroeconomic variables may be useful as predictors of currency risk exposures. Our results are robust to a number of alternative specifications.